Prosthetic Rehabilitation of a Pediatric Patient with an Ocular Defect - Nalawade, Triveni Mohan (Jaypee Brothers Medical Publishers, 2013)
The eye is a vital organ for vision and an important component of facial expression. Loss of an eye has a crippling effect physically and psychologically. Especially, in case of a child where it affects the parent too and the approach toward these special children needs to be very special indeed. The construction of an ocular prosthesis for a child is the same as for an adult. A growing child will require periodic enlargement of the prosthesis in order to accompany the expansion of the anophthalmic cavity and it is the only way to esthetically rebuild the anophthalmic socket. Although implant eye prosthesis has superior outcome, due to economic factors it may not be advisable in all patients. Therefore, an acrylic custom-made ocular prosthesis replacement as soon as possible is a good alternative to promote physical and psychological healing for the patient and to improve social acceptance. A case of a custom fabricated ocular acrylic prosthesis using the advantages of digital photography is presented here, which had acceptable fit, retention and improved esthetics with a certain degree of motility in coordination with the contralateral normal eye. How to cite this article: Nalawade TM, Mallikarjuna RM, Anand BM, Anand M, Shashibhusan KK, Subba Reddy VV. Prosthetic Rehabilitation of a Pediatric Patient with an Ocular Defect. Int J Clin Pediatr Dent 2013;6(1):62-65.